Management of Ovarian Cancer in Elderly - K. Giri, Sushil; Nayak, Bhagyalaxmi (Reviews on Recent Clinical Trials, 2015)
As a result of increasing life expectancy, the cancer incidence in older population is on the rise. Ovarian cancer (OC) is predominantly the disease of elderly women. More than half of all OC occur in women older than 65years. The incidence of the disease increases with the advancing age, peaking during 7th decade of life and remains elevated until the age of 80 years. With the changing demographic scenario the percentage of elderly patients is increasing and gynaecologic oncologists need to focus more on these patients and their specific needs. Due to their higher risk of morbidity and mortality compared to younger patients, elderly patients with advanced ovarian cancer are challenging to treat and are often treated less radically. Their outcome is impaired despite no consistent prognostic effect of age itself. To offer optimal radical management of the elderly women with ovarian cancer and to avoid suboptimal treatment, biological age and functional status need to be considered before individualized treatment plans are defined. Pretreatment assessment can be achieved by using different assessment tools. Patients can tolerate surgery and chemotherapy, as long as they are individually assessed for their medical, psychological, and functional capabilities before therapeutic intervention is initiated. Prospective trials involving elderly women with ovarian cancer are the need of the day to offer justified evidenced based optimal treatment for those who will be benefited from the treatment.
Keywords: ECOG